Molecular interactions between Neisseria meningitidis and its human host. (13th June 2019) - Coureuil, Mathieu; Jamet, Anne; Bille, Emmanuelle; Lécuyer, Hervé; Bourdoulous, Sandrine; Nassif, Xavier
Abstract: Neisseria meningitidis is a Gram‐negative bacterium that asymptomatically colonises the nasopharynx of humans. For an unknown reason, N .  meningitidis can cross the nasopharyngeal barrier and invade the bloodstream where it becomes one of the most harmful extracellular bacterial pathogen. This infectious cycle involves the colonisation of two different environments. (a) In the nasopharynx, N .  meningitidis grow on the top of mucus‐producing epithelial cells surrounded by a complex microbiota. To survive and grow in this challenging environment, the meningococcus expresses specific virulence factors such as polymorphic toxins and MDAΦ. (b) Meningococci have the ability to survive in the extra cellular fluids including blood and cerebrospinal fluid. The interaction of N .  meningitidis with human endothelial cells leads to the formation of typical microcolonies that extend overtime and promote vascular injury, disseminated intravascular coagulation, and acute inflammation. In this review, we will focus on the interplay between N .  meningitidis and these two different niches at the cellular and molecular level and discuss the use of inhibitors of piliation as a potent therapeutic approach.